(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2023)
With the movements of the streets and the constant socio-technical transformations, the newsstands conventionally used to commercialize printed titles were redimensioned amidst the urgent temporal and social instabilities in the possible relationships of each place. Paying attention to the adaptability of the newsstands due to the urban contexts, this article focuses on the newsstands we have come across in exploratory journeys in cities of seven states of Brazil in order to reflect on “the lives of the newsstands” and think them as communicational environments that admit different formats due to the crossings with the spaces that constitute them and taking them as constituent agents of the spaces.